A millennial‐scale chronicle of evolutionary responses to cultural eutrophication in Daphnia. (8th January 2014) - Frisch, Dagmar; Morton, Philip K.; Chowdhury, Priyanka Roy; Culver, Billy W.; Colbourne, John K.; Weider, Lawrence J.; Jeyasingh, Punidan D.; Post, David
Abstract For an accurate assessment of the anthropogenic impacts on evolutionary change in natural populations, we need long‐term environmental, genetic and phenotypic data that predate human disturbances. Analysis of c. 1600 years of history chronicled in the sediments of South Center Lake, Minnesota, USA, revealed major environmental changes beginning c. 120 years ago coinciding with the initiation of industrialised agriculture in the catchment area. Population genetic structure, analysed using DNA from dormant eggs of the keystone aquatic herbivore, Daphnia pulicaria, suggested no change for c. 1500 years prior to striking shifts associated with anthropogenic environmental alterations. Furthermore, phenotypic assays on the oldest resurrected metazoan genotypes (potentially as old as c. 700 years) indicate significant shifts in phosphorus utilisation rates compared to younger genotypes. Younger genotypes show steeper reaction norms with high growth under high phosphorus (P), and low growth under low P, while 'ancient' genotypes show flat reaction norms, yet higher growth efficiency under low P. Using this resurrection ecology approach, environmental, genetic and phenotypic data spanning pre‐ and post‐industrialised agricultural eras clearly reveal the evolutionary consequences of anthropogenic environmental change.